If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=(2H+9)=(5H-3)=(3H+2)=7106
We move all terms to the left:
-((2H+9))=0
We calculate terms in parentheses: -((2H+9)), so:We get rid of parentheses
(2H+9)
We get rid of parentheses
2H+9
Back to the equation:
-(2H+9)
-2H-9=0
We move all terms containing H to the left, all other terms to the right
-2H=9
H=9/-2
H=-4+1/2
| 2x+(4+x)=2(x+4)+17 | | 2(x+4)-2x=17 | | j+-13=-33 | | 3z+12=9z-16 | | 2y+3(5y−7)=47 | | 2/5=30/n | | 4v=-7 | | 4x+4(-5x+7)=172 | | 32 w=12 | | 7b+2=3b+30# | | 4x−2(x+9)=6 | | 3w+12=6w+17 | | 2-n=6-18 | | 5n=-105 | | 4y+8=2y-30 | | 6(x−1)+8=32 | | 3x+6=9x+47 | | 2/3x+2/3x9=8 | | −8=−2x+11 | | -0.375c-11=13= | | 7x+2(5x-14)=-113 | | -6x+5=89 | | 20w=10 | | 12(x-3)-1=5(-x+8)+4 | | 5a+36=9 | | 5m+4=m8 | | 8x/3=x+20 | | 4b+3=2b=11 | | -201=3x-4(-5x-13) | | (5x)^2=x+3 | | 50r+4=12.50 | | 2.50r+4=12.50 |